2021
DOI: 10.3389/fphar.2021.653272
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ASIC1a-Mediated ERS Improves the Activation of HSCs and Copper Transport Under Copper Load

Abstract: Hepatolenticular degeneration (HLD) is an autosomal recessive genetic disease caused by the toxic accumulation of copper in the liver. Excessive copper will disrupt the redox balance in cells and tissues, causing ischemia, hypoxia, and inflammation. Acid-sensitive ion channel 1a is a cationic channel activated by extracellular acid and allowing Ca2+ and Na+ to flow into cells. Its expression appears in inflammation, arthritis, fibrotic tissue, and damaged environment, but its role in hepatolenticular degenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…At various time points, 1 milliliter of venous blood was collected and transferred to EP tubes. The samples were placed in a 4°C refrigerator overnight and then centrifuged at 3,000 revolutions per minute for 15 minutes at 4°C [47], the upper serum layer was retained while the rest was discarded. Follow the instructions on the ELISA kits [31,48].…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…At various time points, 1 milliliter of venous blood was collected and transferred to EP tubes. The samples were placed in a 4°C refrigerator overnight and then centrifuged at 3,000 revolutions per minute for 15 minutes at 4°C [47], the upper serum layer was retained while the rest was discarded. Follow the instructions on the ELISA kits [31,48].…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Therefore, the early occurrence of hepatolenticular degeneration is the same as that of liver fibrosis. Kong et al ( 115 ) induced HSC-T6 activation with CuSO 4 , and found that ASIC1a was highly expressed in activated HSC-T6 cells. They speculated that ASIC1a played a role in promoting the process of hepatolenticular degeneration fibrosis.…”
Section: Pathology Of Asics In the Digestive Systemmentioning
confidence: 99%
“…Recently, increasing studies revealed that circRNAs were deeply involved in malignancy ( 2 ). CircRNA_103801 induces osteosarcoma proliferation, migration, and invasion processes by mediating miR-338-3p ( 3 ). CircTADA2A accelerates the malignant progression of osteosarcoma via modulating miR-203a-3p ( 4 ).…”
Section: Introductionmentioning
confidence: 99%